2017
DOI: 10.1016/j.conb.2017.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Sleep regulation of the distribution of cortical firing rates

Abstract: Sleep is thought to mediate mnemonic and homeostatic functions. However, the mechanism by which this brain state can implement both the “selective” plasticity needed to consolidate novel memory traces as well as the “general” plasticity necessary to maintain a well-functioning neuronal system is unclear. Recent findings show that both of these functions differentially affect neurons based on their intrinsic firing rate, a ubiquitous neuronal heterogeneity. Furthermore, they are both implemented by the NREM slo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
55
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(68 citation statements)
references
References 65 publications
(66 reference statements)
7
55
0
Order By: Relevance
“…Since REM sleep is related to spine elimination during development [114], the increased firing rate during waking towards the set-point showed by [243] may be sustained by sleep-dependent structural changes, since they do not return to the previous firing pattern after complete sleep epochs. Although other homeostatic processes may participate as neuronal regulation of intrinsic excitability [246], they may be also sleep-dependent [247].…”
Section: Sleep-dependent Cortical Plasticity During Developmentmentioning
confidence: 99%
“…Since REM sleep is related to spine elimination during development [114], the increased firing rate during waking towards the set-point showed by [243] may be sustained by sleep-dependent structural changes, since they do not return to the previous firing pattern after complete sleep epochs. Although other homeostatic processes may participate as neuronal regulation of intrinsic excitability [246], they may be also sleep-dependent [247].…”
Section: Sleep-dependent Cortical Plasticity During Developmentmentioning
confidence: 99%
“…Simultaneous EEG (two channels, band filtered at 0.1-100 Hz) and multi-unit recordings (one-channel, band filtered 300-2000 Hz) (both in current-clamp mode) data along with one channel EMG recordings(400 Hz) were collected by using two multiClamp 700B amplifiers (total 4 channels, Molecular devices Inc., Union City, CA) and Clampex 10 software (Molecular Devices Inc., Union City, CA), and digitized at 20 kHz using a Digidata 1440A. (Kandel & Buzsaki, 1997;Levenstein et al, 2017)) were applied]. The injected current amplitudes(pA) and duration were chosen to avoid kindling effect which needs larger currents within uA amplitude range (Lothman et al, 1990;Racine, 1972aRacine, , 1972b.…”
Section: Data Collection and Analysismentioning
confidence: 99%
“…A series of recent studies have demonstrated that sleep has heterogeneous effects on neuronal firing rates within neural circuits. Specifically, initially highly active neurons reduce their firing rates across a period of sleep, while sparsely firing neurons simultaneously increase their firing rate (4,5,30). Sleep is essential for this redistribution of firing rates, as firing rate changes do not occur in animals that are experimentally sleep deprived (5).…”
Section: Input-dependent Phase Locking Of Firing To Network Oscillatimentioning
confidence: 99%
“…While certain features of information storage may be localized to specific cell populations (e.g., location information encoded in hippocampal place cell activity), in general, localizing memory traces to specific neural circuits has been an elusive task (2). Furthermore, recent data indicate that engrams are formed from neuronal populations which are vastly heterogeneous in terms of their firing patterns, with log-normal distributions of firing rates ranging over many orders of magnitude (4,5). These populations appear to encode different aspects of experience (5)(6)(7) and may exhibit different dynamics during memory consolidation processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation